Why Pragmatics and Theory of Mind Do Not (Completely) Overlap - Bosco, Francesca M.; Tirassa, Maurizio; Gabbatore, Ilaria (Frontiers in Psychology, 2018)
Aim of the paper is to discuss the extent to which pragmatics, i.e. the ability to use language and other expressive means to convey meaning in a specific context, overlaps with Theory of Mind (ToM), i.e. the ability to ascribe mental states to oneself and the others. We discuss empirical data available in the current literature concerning the relation between these two faculties, with specific reference to the developmental and clinical domains. Part of the literature we take into account shows that ToM correlates with pragmatic ability; however, other studies show that pragmatic ability alone cannot explain the empirical differences of performance across different kinds of pragmatic tasks. We conclude that to conceive pragmatics as a sort of subcomponent of ToM, and thus to collapse or reduce the notion of pragmatics into the (wider) notion of ToM, is not theoretically correct and a possible cause of methodological confusion in the relevant empirical research.